Metodologi Al-Hafiz Ibn Al-Salah Dalam Permasalahan Pentashihan Hadis Dan Fenomena Pentashihan Pada Masa Kini - Zulhilmi Mohamed Nor (Universiti Sains Islam Malaysia, 2024)
It is beyond doubt that al-Ḥāfiẓ Ibn Ṣalaḥ is regarded by scholars of ḥadīth as a founding father, a pioneer in the new arrangement of terminology of ḥadīth (Muṣṭalaḥ al-Ḥadīth). Most of ḥadīth scholars that appeared after his reign will commonly utilised the new framework of ḥadīth studies based on Ibn Ṣalaḥ’s arrangement. One of Ibn Ṣalaḥ’s popular argument in ḥadīth authentication (taṣḥīḥ al-ḥadīth) is that, he appeared as always disregarding the ability of new scholars in authenticating a ḥadīth. For him, any status of ḥadīth that has been given by the previous scholars (al-mutaqaddimūn) is well enough to be used and argues the need to accept any new judgement by later scholar (al-muta’akhirūn). This idea has been the centre of disputation among scholars of ḥadīth. Thus, this study aims to (1) explore scholars’ opinion on the concept of ḥadīth authentication, (2) analyse Ibn Ṣalaḥ’s notion on this particular subject and (3) examine contemporary scholars’ opinion on this issue. The present study employs qualitative method in which textual analysis was used as its main mechanism in scrutinising the issue. The study it is finding argues that, indeed, the previous scholars (al-mutaqaddimūn) plays an important role in justifying a status of ḥadīth, but is does not deny the important roles of al-muta’akkhirūn and their contribution in the process of ḥadīth authentication.